The effect of perceptual skill of RFT scores : a cross-cultural study - Marais, W F (Rhodes University, Faculty of Humanities, Department of Psychology, 1977)
The increasing need to select individuals for tasks suited to their personality make-up, has added to the challenge psychology faces of developing tests which can be applied to subjects from different cultures and environments. Many attempts at such designs litter the history of industrial and cross- cultural personality research. Among those to have survived years of reassessment, is the cognitive style approach developed by Herman Witkin. Intro., p. 1.
Keywords: Witkin, Herman A; Personality; Personality and culture -- Cross-cultural studies; Cross-cultural studies; Perception